Psikologi Pendidikan dalam Proses Belajar Mengajar - Sukatin; Khofiza Irly Fatriha; Nurhafizin; Romayani; Yeri Anggara Dirta (Citra Dharma Cindekia, 2023)
Educational psychology is a science that studies learning, behavior, growth, and individual maturity as well as the application of scientific principles to human reactions which basically affect the process of teaching and learning in the world of education. Educational psychology can be used as a foundation in the development of educational theory and practice and has made a major contribution to education. Educational psychology focuses on the way children learn in educational settings, the effectiveness of teaching, teaching methods, and the organizational management of schools. Teachers or education personnel are an important element in applying educational psychology to children. Educational psychology in children is very important to note because it has a big influence on children's learning processes, to help children so that their learning processes run effectively. Teachers or educators must understand how to carry out better and meaningful learning practices. Learning practices in which teachers can understand students' psychological conditions, how they behave, what factors can encourage their potential to be more open, and other things in line with the learning objectives themselves. This reason also makes Educational Psychology a field that must be mastered by teachers or educators, so that they have various perspectives and do not rely on only one assumption when encountering certain problems in learning.